Reliability of Isometric Knee Extension Muscle Strength Measurements of Healthy Elderly Subjects Made with a Hand-held Dynamometer and a Belt - Isozaki, Koji; Katoh, Munenori (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to examine the reliability of three isometric knee extension strength measurements (IKE) made with a hand-held dynamometer (HHD) and a belt of healthy elderly living in the community as subjects. [Subjects] The subject cohort consisted of 186 healthy elderly people, aged 65 to 79 years, living in local communities. [Methods] IKE of the leg subjects used to kick a ball was measured. IKE of each subject was measured three times using an HHD-belt at intervals of 30 seconds. The reliability of the larger of the first two measurements (LV2) as well as the third measurement (3V) was investigated. [Results] The intraclass correlation coefficients [ICC (1, 1)] for LV2 and 3V were 0.955. Bland-Altman analysis showed a fixed bias, and the limits of agreement ranged from −5.6 to 4.6. [Conclusion] The ICC results show that the test-retest reproducibility of IKE measurements of healthy elderly subjects using an HHD-belt is high. However, Bland-Altman analysis showed a fixed bias, suggesting the need for three measurements.